352 Robot-Assisted Endoscopic Third Ventriculostomy. (August 2016) - Hoshide, Reid; Calayag, Mark; Meltzer, Hal S.; Levy, Michael L.; Gonda, David D.
Abstract : INTRODUCTION: Endoscopic third ventriculostomy (ETV) is an established and effective treatment for obstructive hydrocephalus. In its most common application, surgeons plan their entry point and endoscope trajectory for the procedure based on anatomic landmarks, then free-handedly control the endoscope. We have introduced the Rosa robot assistance to our ETV procedure to stereotactically optimize endoscope trajectories, to reduce risk of traction on neural structures by the endoscope, and to provide a stable mechanical holder of the endoscope. Here, we present our series of Rosa robot-assisted ETVs. METHODS: At our institution, we performed Rosa robot-assisted ETVs on 6 consecutive subjects within a 3-month period. Patients had to have a favorable expected response to ETV (ETV success score = 70) without additional endoscopic procedures (eg, choroid plexus cauterization, septum pellucidum fenestration). The modality of image registration (CT, MRI, surface mapping, or bone fiducials) was dependent on the case. RESULTS: Six total pediatric subjects with an age range of 2 to 14 years, 2 females and 4 males, ETV success score ranging from 70 to 90, underwent successful ETV surgery with Rosa robotic assist within a 3-month period. Their intracranial pathologies included tectal gliomas (n = 3), aqueductal stenosis (n = 1), posthemorrhagic hydrocephalus (n = 1), and communicating hydrocephalus (n = 1). Robot assistance was limited to the ventricular access in the first 2 procedures but was used for the entirety of the procedure for the following 4 cases. Four of these cases were combined with another procedural objective (2 stereotactic tectal mass biopsies, 1 Chiari decompression, and 1 ventriculoperitoneal shunt removal with EVD placement). A learning curve was observed with each subsequent surgery because registration and surgical times were shorter and more efficient. All subjects had complete resolution of their preprocedural symptoms. There were no complications. CONCLUSION: Assistance with the Rosa robot provides a safe, stable, precise, and minimally invasive approach to ETVs.